PENERAPAN METODE INKUIRI DALAM PEMBELAJARAN IPA DI SDN TOMINI - Moh Aji Pangestu; Arda Arda (Program Studi Tadris Ilmu Pengetahuan Alam, Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Institut Agama Islam Negeri (IAIN) Palu, 2020)
This research aims to determine the application of the inquiry method in science learning at SDN Tomini. This research is pre-experimental study with one group pretest-postest design. Subjects of this research were 23 students of fifth grade SDN Tomini. Data collection was carried out through pretest and posttest. The gain based on the result of data analysis were 0,598. It means that there is improvement on the students learning outcomes after learning science with the inquiry method in medium category. The One Sample T-Test obtained the t value of 6,634 and Sig. (2-tailed) 0,000. This value indicates that the hypothesis H1 is accepted. It means that the average value of students after learning science by inquiry method is higher than minimum completeness criteria.